The Effect Of Intraoperative Use Of Dexmedetomidine During The Daytime Operation Vs The Nighttime Operation On Postoperative Sleep Quality And Pain Under General Anesthesia - Song B (Dove Medical Press, 2019)
Bijia Song, Yang Li, Xiufei Teng, Xiuyan Li, Yanchao Yang, Junchao Zhu Department of Anesthesiology, Shengjing Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Junchao ZhuDepartment of Anesthesiology, Shengjing Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of ChinaEmail zhujunchao1@hotmail.comObjectives: The aim of our study was to compare the effect of using dexmedetomidine (DEX) during the daytime operation or the nighttime operation under general anesthesia on postoperative sleep quality and pain of patients.Methods: Seventy-five patients scheduled for elective laparoscopic abdominal surgeries under general anesthesia were randomly assigned to receive operation in the Day Group (8:00–12:00) and the Night Group (18:00–22:00). The Portable Sleep Monitor (PSM) was performed on the following 3 nights: the night before surgery (Sleep 1), the ﬁrst night after surgery (Sleep 2), and the third night after surgery (Sleep 3). Postoperative pain scores using visual analogue scoring scale, subjective sleep quality using the Athens Insomnia Scale, total dose of general anesthetics and PCA pump press numbers were also recorded.Results: Intraoperative administration of DEX for patients in the Day Group could improve sleep quality with a higher sleep efficiency and a lower AIS subjective sleep quality than patients in the Night Group at Sleep 2 (P < 0.001 and P = 0.001, respectively) and Sleep 3 (P < 0.001, respectively). There were marked lower rapid eye movement (REM) sleep and Stable sleep in the Night Group than that in the Day Group at Sleep 2 (P < 0.001 and P = 0.032, respectively) and Sleep 3 (P < 0.001, respectively). Patients in the Day Group have better pain relief and less PCA pump press numbers than patients in the Night Group.Conclusion: Using dexmedetomidine during the daytime operation can better improve postoperative sleep quality and pain than nighttime operation in patients undergoing laparoscopic abdominal surgeries.Keywords: dexmedetomidine, sleep quality, general anesthesia, postoperative pain